Mutations in eukaryotic 18S ribosomal RNA affect translational fidelity and resistance to aminoglycoside antibiotics. - Chernoff, Y O (1994)
Mutations have been created in the Saccharomyces cerevisiae 18S rRNA gene that correspond to those known to be involved in the control of translational fidelity or antibiotic resistance in prokaryotes. Yeast strains, in which essentially all chromosomal rDNA repeats are deleted and all cellular rRNAs are encoded by plasmid, have been constructed that contain only mutant 18S rRNA. In Escherichia coli, a C-->U substitution at position 912 of the small subunit rRNA causes streptomycin resistance. Eukaryotes normally carry U at the corresponding position and are naturally resistant to streptomycin. We show that a U-->C transition (rdn-4) at this position of the yeast 18S rRNA gene decreases resistance to streptomycin. The rdn-4 mutation also increases resistance to paromomycin and G-418, and inhibits nonsense suppression induced by paromomycin. The same phenotypes, as well as a slow growth phenotype, are also associated with rdn-2, whose prokaryotic counterpart, 517 G-->A, manifests itself as a suppressor rather than an antisuppressor. Neither rdn-2- nor rdn-4-related phenotypes could be detected in the presence of the normal level of wild-type rDNA repeats. Our data demonstrate that eukaryotic rRNA is involved in the control of translational fidelity, and indicate that rRNA features important for interactions with aminoglycosides have been conserved throughout evolution.